Dislocation electron tomography: A technique to characterize the dislocation microstructure evolution in zirconium alloys under irradiation. (July 2021) - Mussi, Alexandre; Addad, Ahmed; Onimus, Fabien
Abstract: Diffraction-contrast electron tomography was used to analyse the 3D geometry of the dislocation microstructure in a zirconium alloy before and after ion irradiation. The material had been strained at room temperature prior to irradiation. After straining, the material exhibited mainly screw dislocations with Burgers vectors. From the analysis of the habit plane of dislocations with non-screw segments, it was deduced that they have glided mainly in the prismatic planes and to a lesser extent in the first order pyramidal planes. After irradiation, dislocation loops with Burgers vectors were observed. It was shown that the loops are not pure edge and have their habit plane located around the planes { 10 1 ¯ 0 }, tilted up to 20° towards the planes (0001) and { 11 2 ¯ 0 } . Furthermore, it was proven that the initial screw dislocations have climbed under irradiation. Several dislocations were also found to have interacted with loops during climb. The climb of dislocations under irradiation is an important mechanism that can explain part of the in-reactor deformation of zirconium alloys when subjected to simultaneous mechanical loading and irradiation. Interactions between dislocations and loops occurring during dislocation climb may also play a significant role on the in-reactor deformation of zirconium alloys. Graphical abstract: Image, graphical abstract